2017
DOI: 10.1289/ehp291
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Cord Blood Oxylipins and Exposure to Particulate Matter in the Early-Life Environment: An ENVIR ON AGE Birth Cohort Study

Abstract: Background:As part of the lipidome, oxylipins are bioactive lipid compounds originating from oxidation of different fatty acids. Oxylipins could provide a new target in the developmental origins model or the ability of early life exposure to change biology.Objectives:We studied the association between in utero PM2.5 (particulate matter with aerodynamic diameter < 2.5 μm) exposure and oxylipin profiles in newborns.Methods:Thirty-seven oxylipins reflecting the cyclooxygenase (COX), lipoxygenase (5-LOX and 12/15-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
(52 reference statements)
1
19
0
Order By: Relevance
“…The possibility of taking into account chronic exposures is relevant for the study of a large number of biological pathologies and mechanisms [55]. Moreover, several recent studies have shown the need to study exposures accurately over short periods and specific exposure windows [56]. Ren et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of taking into account chronic exposures is relevant for the study of a large number of biological pathologies and mechanisms [55]. Moreover, several recent studies have shown the need to study exposures accurately over short periods and specific exposure windows [56]. Ren et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in targeted lipidomics provide the ability to better characterize several eicosanoids from distinct biosynthetic pathways. However, few studies to date have investigated comprehensive panels of eicosanoids (i.e., including several biosynthetic pathways) during pregnancy [17,20,21], and none to our knowledge have examined patterns in eicosanoid levels across pregnancy. In this study we aimed to characterize repeated measurements of eicosanoids during pregnancy and assess associations with infant size at delivery (SGA and LGA) in a subset of women from an ongoing prospective birth cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Although several analytical HRM platforms exist, we have utilized an approach based on liquid chromatography coupled with high-resolution mass spectrometry, which have the capability of identifying tens of thousands of metabolic features. We (Ladva et al, 2017), and others (Breitner et al, 2016; Martens et al, 2017; Menni et al, 2015; Surowiec et al, 2016; Vlaanderen et al, 2017), have begun to examine the capability of HRM to capture metabolic perturbations following exposures to ambient air pollutants. Currently, analytical and scientific uncertainties in HRM application, however, have limited its use for measuring the response to exposures from individual sources, such as TRAP (Hines et al, 2007; Morrison et al, 2007).…”
Section: Introductionmentioning
confidence: 99%